The global impact of COVID-19 on tuberculosis: A thematic scoping review, 2020-2023. - Michael H Marco; Sevim Ahmedov; Kenneth G Castro (PLOS Global Public Health)
Background This thematic scoping review of publications sought to understand the global impact of COVID-19 on tuberculosis (TB), interpret the scope of resonating themes, and offer policy recommendations to stimulate TB recovery and future pandemic preparedness. Data sources Publications were captured from three search engines, PubMed, EBSCO, and Google Scholar, and applicable websites written in English from January 1, 2020, to April 30, 2023. Study selection Our scoping review was limited to publications detailing the impact of COVID-19 on TB. Original research, reviews, letters, and editorials describing the deleterious and harmful--yet sometimes positive--impact of COVID-19 (sole exposure) on TB (sole outcome) were included. The objective was to methodically categorize the impacts into themes through a comprehensive review of selected studies to provide significant health policy guidance. Data extraction Two authors independently screened citations and full texts, while the third arbitrated when consensus was not met. All three performed data extraction. Data synthesis/results Of 1,755 screened publications, 176 (10%) covering 39 countries over 41 months met the inclusion criteria. By independently using a data extraction instrument, the three authors identified ten principal themes from each publication. These themes were later finalized through a consensus decision. The themes encompassed TB's care cascade, patient-centered care, psychosocial issues, and health services: 1) case-finding and notification (n = 45; 26%); 2) diagnosis and laboratory systems (n = 19; 10.7%) 3) prevention, treatment, and care (n = 22; 12.2%); 4) telemedicine/telehealth (n = 12; 6.8%); 5) social determinants of health (n = 14; 8%); 6) airborne infection prevention and control (n = 8; 4.6%); 7) health system strengthening (n = 22; 13%); 8) mental health (n = 13; 7.4%); 9) stigma (n = 11; 6.3%); and 10) health education (n = 10; 5.7%). Limitations Heterogeneity of publications within themes. Conclusions We identified ten globally generalizable themes of COVID-19's impact on TB. The impact and lessons learned from the themed analysis propelled us to draft public health policy recommendations to direct evidence-informed guidance that strengthens comprehensive global responses, recovery for TB, and future airborne pandemic preparedness.